2008
DOI: 10.1177/1077559508321272
|View full text |Cite|
|
Sign up to set email alerts
|

Can Technology and the Media Help Reduce Dysfunctional Parenting and Increase Engagement With Preventative Parenting Interventions?

Abstract: The studies aimed to evaluate the effectiveness of the Triple P-based "Driving Mum and Dad Mad" television series in improving positive parenting behaviours and child wellbeing over a six month period. A secondary aim was to compare the effectiveness of the intervention with (enhanced condition) and without (standard condition) extra support and resources. The influence of demographic details and parenting background were recorded to check for effects on outcomes and compliance. HypothesesParticipants were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(108 citation statements)
references
References 38 publications
4
102
0
2
Order By: Relevance
“…Il prend aussi en compte les besoins de familles très variées et les innovations récentes ont étendu la gamme des modalités de diffusion du programme [7]. En plus des traditionnels programmes de groupes et individuels, les parents ont la possibilité d'apprendre et de pratiquer leurs compétences parentales avec des cahiers d'exercices et un soutien par téléphone [23], par l'intermédiaire d'un site internet [24] ou encore d'une émission télévisée [25]. La transmission des informations via différents médias semble favorable à la participation des groupes plus difficiles à atteindre et la démarche des parents est vécue comme moins stigmatisante [20].…”
Section: Obstacles à La Participation Aux Programmes Parentauxunclassified
“…Il prend aussi en compte les besoins de familles très variées et les innovations récentes ont étendu la gamme des modalités de diffusion du programme [7]. En plus des traditionnels programmes de groupes et individuels, les parents ont la possibilité d'apprendre et de pratiquer leurs compétences parentales avec des cahiers d'exercices et un soutien par téléphone [23], par l'intermédiaire d'un site internet [24] ou encore d'une émission télévisée [25]. La transmission des informations via différents médias semble favorable à la participation des groupes plus difficiles à atteindre et la démarche des parents est vécue comme moins stigmatisante [20].…”
Section: Obstacles à La Participation Aux Programmes Parentauxunclassified
“…However, some measure of behavior change was assessed in more than half (58.8%) of the studies [46,47,[49][50][51][52][53][56][57][58][59]. Significant decreases were seen in child behavior problems [47,[57][58][59] and in dysfunctional or coercive parenting behaviors [47,51,57,59]. Two studies reported increases in calls to helplines to report child abuse cases [46,52].…”
Section: Outcome Evaluationmentioning
confidence: 99%
“…Only three studies examined child abuse outcomes specifically and found a reduction in the incidence of abusive head injuries [49], child maltreatment injuries [56] and child maltreatment cases [52,56]; though one was not statistically significant [52]. However, some measure of behavior change was assessed in more than half (58.8%) of the studies [46,47,[49][50][51][52][53][56][57][58][59]. Significant decreases were seen in child behavior problems [47,[57][58][59] and in dysfunctional or coercive parenting behaviors [47,51,57,59].…”
Section: Outcome Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, novel research trials evaluating the effects of viewing a publicly-aired six-week television series ("Driving Mum and Dad Mad"), documenting the experiences of families attending Triple P (Calam, Sanders, Miller, Sadhnani, & Carmont, 2008), have found positive outcomes, although this is not a disseminated resource within the core Triple P framework.…”
Section: Web-based Parenting Programs: An Overview Of the Field And Cmentioning
confidence: 99%